Project FIERCE: Exploring the Students’ Perspective and Behavior towards Research Subject - Mapanoo, Jerick E. (Future Science / FSH-PH Publications, 2023)
To support and achieve the goals and objectives of the Department of Education, the researcher conducted seminar entitled Project FIERCE. The main purpose of this research was to determine the students’ perspective and behavior towards research subject relative to the conduct of Project FIERCE. The study made use of the phenomenological type of qualitative approach, and the findings were drawn from semi-structured interviews. The nine (9) participants are all Senior High School students from New Taugtog National High School who completed and participated in three (3) - day seminar. Participants were asked about in what ways their perception and behavior regarding the research subject changed after participating in Project FIERCE seminar. It was found out that participants of the project FIERCE seminar gained knowledge and experience in research subjects, which resulted in a significant decrease in stress and a marked increase in confidence. This indicates the positive impact of Project FIERCE on research perspective and behavior. This research further concluded through Project FIERCE seminar, the participants acknowledged that the tasks in research subject can still be difficult, but they felt more capable and ready to take on challenges. With this positive result, it may lead to the success of attaining K-12 goals and objectives. Thus, it is highly recommended that the Department of Education should continue programs and policies that would support and provide seminars similar to Project FIERCE, which increase the perspection and behavior of students towards research subject.